Gaining competitive advantage through new product development capability in Malaysian Government Linked Companies - Nik Herda Nik Abdullah (Indonesian Journal of Economics, Social, and Humanities, 2019)
A new product development capability can be shown through organisational routines that shape the processes of innovation, which are aimed to reconfigure a firm’s product portfolio. It is aimed to create a concrete physical asset from an idea and this relates to the innovation that is the mechanism by which firms to produce new products, processes and systems that essential in order to adapt market changes, technologies and types of competition. New product development capability aids corporate managers plan and execute strategies successfully while securing sustainable competitive advantages. This paper aims to explore the extent of top management emphasis on the measures of new product development that are deemed important for business survival and sustainability in the context of Malaysian government-linked companies (GLCs). A questionnaire survey was distributed with a response rate of 47%. Findings revealed that design a high quality of product or service is the most important measures. This revealed that it is a common exercise for Malaysian GLCs to put high emphasis on the importance of the quality of the new products or services.